Crohn disease: Identification, diagnosis, and clinical management. Issue 12 (December 2021) - Snyder, Elizabeth F.; Davis, Stephanie; Aldrich, Kristina; Veerabagu, Manjakkollai; Larussa, Tiziana; Abenavoli, Ludovico; Boccuto, Luigi
Abstract : Abstract: Crohn disease is an inflammatory bowel disorder affecting children and adults. With its increasing prevalence, healthcare providers need adequate resources to assist with diagnosis and management. This article discusses early diagnosis, disease severity and classification, familial predisposition and genomics, and clinical management in the primary care setting. Abstract : Crohn disease is an inflammatory bowel disorder affecting children and adults. With its increasing prevalence, healthcare providers need adequate resources to assist with diagnosis and management. This article discusses early diagnosis, disease severity and classification, familial predisposition and genomics, and clinical management in the primary care setting.